Thermo-mechanical control of residual stress, distortion and microstructure in wire + arc additively manufactured Ti-6Al-4V. - Hönnige, Jan Roman (Cranfield University, 2018)
Wire + arc additive manufacturing (WAAM), unlike most other additive techniques, targets the manufacture of near-net-shape parts for large-scale structural components with medium complexity. WAAM is of special interest for the aerospace industry for reducing lead-time, material and process costs. Ti−6Al−4V is one alloy that could potentially benefit most from the advantages of WAAM, due to high material and process costs, and is therefore the main scope of this research. The manufacture of critical-use components for civil aviation requires a high process control to provide consistently strong and isotropic mechanical properties, as well as the elimination of residual stresses. Cold work can manipulate and counteract residual stresses caused by the additive process. When applied between two layers (i.e. between the deposition passes → interpass) it was found to refine the microstructure and thereby significantly improve the mechanical properties. So far it was only understood that it can theoretically control both residual stress and microstructure, but the science behind the process and how different parameters influence the effectiveness was only proposed. The present research demonstrates how cold work can be used effectively to address both issues, by identifying the process-relevant mechanisms. Before manipulating residual stresses, their development needed to be investigated Behaviour that had only been predicted using numerical simulations was measured for the first time using neutron diffraction and contour method stress determination techniques. This behaviour includes the development of residual stress during the deposition of straight walls and intersections, stress redistribution upon distortion after unclamping and the potential of thermal stress relief. Analogies to previous findings on steel helped explain the findings. The knowledge of stress development finally helped the development of an analytical model to predict residual stress and distortion, as well as stress redistribution upon unclamping. The performance and parameters of plastic deformation strategies were investigated using various characterisation techniques. Those include hardness mapping, residual stress measurements using hole-drilling and the contour method, electron-backscatter-diffraction (EBSD) plastic strain mapping, heat treatment, as well as numerical simulations to compare against the respective measurement techniques. The methodology allowed the development of parameters that produce the required amount of plastic deformation into the required depth of the material, for different thermal histories. Even though 6 % to 8 % of plastic strain can allow reorientation and the development of finer grains, 12 % of plastic strain or more is probably required to achieve a desired grain size. This value is equivalent to 4° lattice misorientation using an EBSD strain mapping technique and it is equivalent to an increase of hardness by at least20 HV. Different rolling and one alternative cold working techniques were investigated to address both individual issues, residual stress and microstructure. Side rolling was found to be far more effective on controlling residual stress and distortion than vertical interpass rolling. Profiled vertical inter-pass rolling on the other hand is far more effective to refine the microstructure and improve mechanical properties than flat rolling. Machine Hammer Peening is an alternative cold working techniques that offers a much higher degree of freedom compared to rolling. The proof of concept to integrate peening into additive manufacturing was successful. However, available machine hammer peening tools do not supply the impact energy required to be at eye level with rolling. It is estimated that approximately 5000 mJ would be required to be as effective as rolling with 70 kN. The fast thermal cycle within the heat affected zone during the additive deposition was measured for the first time at different locations, which allowed conclusions regarding the respective and local development of the microstructure. It furthermore helped to better understand the grain refinement mechanism, and the influence of thermal cycles on subsequent undesired grain growth. The research findings can be applied to develop effective inter-pass cold work strategies for arbitrary thermal cycles and they are sufficient to validate numerical simulations to design better process parameters more efficiently.